2014
DOI: 10.4049/jimmunol.1301424
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Pathways of Humoral and Cellular Immunity Induced with the Mucosal Administration of a Nanoemulsion Adjuvant

Abstract: Nasal administration of an oil-in-water nanoemulsion (NE) adjuvant W805EC produces potent systemic and mucosal, Th-1– and Th-17–balanced cellular responses. However, its molecular mechanism of action has not been fully characterized and is of particular interest because NE does not contain specific ligands for innate immune receptors. In these studies, we demonstrate that W805EC NE adjuvant activates innate immunity, induces specific gene transcription, and modulates NF-κB activity via TLR2 and TLR4 by a mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 88 publications
3
46
2
Order By: Relevance
“…8). The SFN adjuvant activates innate immunity, induces specific genes transcription, and modulates NF-κB activity via MAPKs by the mechanisms that appear to be distinct from both the typical toll-like receptors agonists and other adjuvants like alum or MF593334. Firstly, SFN induces ROS in macrophages, indicating SFN can evoke immune response by the ROS-dependent signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…8). The SFN adjuvant activates innate immunity, induces specific genes transcription, and modulates NF-κB activity via MAPKs by the mechanisms that appear to be distinct from both the typical toll-like receptors agonists and other adjuvants like alum or MF593334. Firstly, SFN induces ROS in macrophages, indicating SFN can evoke immune response by the ROS-dependent signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that MyD88 and Toll/IL-1 receptor domain-containing adaptor inducing IFN-b (TRIF), the critical signaling components for TLR, are not necessary for antibody responses. 25,26 These new findings provide new insights into development of mucosal adjuvants.…”
Section: Research and Development Of Mucosal Adjuvantsmentioning
confidence: 92%
“…Due to the use of adjuvants like toll-like receptor agonist and vectors like liposomes and microspheres in clinical trials, advantages were seen in Phase II and Phase III trials (52). Nasal mucosa administration of antigens in the presence of adjuvants like nano-emulsion induced distinct pathways of humoral and cellular immunity (53). CD40, CD80, and CD86 are molecules expressed by DCs that are important for a well-established immune response.…”
Section: Recent Novelties; Lessens From Outside the Nasal Mucosamentioning
confidence: 99%